Hemostatic changes following COVID-19 vaccination: Do they promote a pro-thrombotic state? - Tarinee Rungjirajittranon; Yupa Nakkinkun; Bundarika Suwanawiboon; Yingyong Chinthammitr; Weerapat Owattanapanich; Theera Ruchutrakool (Human Vaccines & Immunotherapeutics)
Vaccine-induced thrombotic thrombocytopenia (VITT) is a unique thrombotic complication of Coronavirus Disease 2019 (COVID-19) immunization, especially with adenovirus vector vaccines. However, non-VITT thrombotic events were seen in mRNA vaccines. We aimed to investigate hemostatic changes following COVID-19 vaccination, and to compare these changes between the ChAdOx1 and BNT162b2 vaccines. We conducted a prospective study involving COVID-19 infection- and vaccination-naïve participants aged over 18 years receiving the ChAdOx1 or BNT162b2 vaccines. Blood samples were collected at pre-vaccination, 7 and 21 days post-vaccination. D-dimer levels, platelet counts, and TGA parameters were collected. ChAdOx1-S group D-dimer levels did not change significantly throughout the study (p = .51). BNT162b2 group median D-dimer levels increased significantly on day 7 [245 ng FEU/mL (IQR 155–384) at baseline; 315 ng FEU/mL (IQR 187.5–412) at day 7; and 271 ng FEU/mL (IQR 166–400) at day 21; p = .021]. BNT162b2 group platelet counts increased significantly on day 7 (p = .010). TGA parameters in the ChAdOx1-S group decreased significantly in ETP levels (p = .007) and peak concentrations (p = .041) over time while those of the BNT162b2 group were stable (median ETP levels and peak concentrations; p > .05). Mean change in ETP levels from pre-vaccination between the vaccines were significantly different at day 21 (p = .001). No anti-platelet factor 4 antibody positivity or clinical thrombosis occurred. Both vaccines showed low thrombosis risk without increased thrombin generation. However, BNT162b2 vaccine recipients exhibited a temporary inflammatory response, evidenced by a brief rise in D-dimer levels.Trial registration TCTR20240812005